I-Gel and LMA classic in the hands of novice: A comparative study - Bhattacharjee, Ishita; Sarkar, Susanta; Bhattacharyya, Chiranjib; Das, Debojyoti; Mandal, Mohanchandra (Asian Journal of Medical Sciences, 2021)
Background: Supraglottic airway devices (SADs) such as LMA classic (cLMA), I-Gel, etc. are indispensable tool for the anaesthesiologists experienced in airway management. But studies evaluating the performance of these devices in the hands of unskilled personnel are scarce. Aims and Objective: To determine the procedure time and the proportion of patients having successful placement of I-gel and LMA classic by first-year Post Graduate Trainees (PGTs) of Anaesthesiology who tried insertion of those devices after a short training in mannequins without any hands-on training regarding placement of the devices in human. Materials and Methods: After getting Institute’s Ethics Committee’s approval for this interventional study, forty adult patients, posted for short surgical or gynaecological surgery, were randomly allocated in to two groups to have placement of either I-Gel (group ‘I’, n=20) or cLMA (group ‘C’, n=20) by first-year PGTs. The procedure time (Primary outcome) i.e. the time taken for successful placement of either device was determined and compared. A standard technique of anaesthesia was followed in every patient. Any adverse event such as sore throat, odynophagia, blood stain on the device, etc. was also recorded. Results: All patients were comparable with respect to demographic data and Mallampati scores. The mean procedure time (seconds) was considerably lower in I-Gel group compared with cLMA (63.3 ± 57.2 versus 163.0 ± 158.3, respectively, P value <0.001). The incidence of successful placement at first attempt was significantly higher for I-Gel group. The incidence of adverse events was comparable. Conclusion: Procedure time for I-Gel insertion is significantly shorter than with LMA Classic along with a higher success rate with first attempt for the former. I-Gel may be a better alternative as airway device for the unskilled anaesthesiologist.